Structural performance of CLT shear connections with castellations and angle brackets. (1st August 2021) - Brown, Justin R.; Li, Minghao; Sarti, Francesco
Highlights: Twenty-nine cross-laminated timber (CLT) castellated joints and six angle bracket joints were tested. Castellated joints shear strength and stiffness were 2.5 and 7 times greater than angle bracket joints. A stiffness based analytical component model was developed to predict castellated joint strength. Large 5-ply (175 mm thick) and 7-ply (275 mm thick) CLT panels were employed. Abstract: The advent of digital fabrication technologies and mass timber products such as cross-laminated timber (CLT) have facilitated the use of traditional carpentry joints in modern mass timber construction. Through contact bearing, mortise and tenon castellated joints can also provide high shear strength and stiffness between timber members when compared to connections using mechanical connectors/fasteners. In this study, a total of 29 connection specimens using carpentry castellations and six connection specimens using commercial angle brackets were tested under monotonic loading to evaluate their structural performance. These specimens used five-ply (175 mm thick) and seven-ply (275 mm thick) CLT panels. It was found that the shear strength and stiffness of the castellated joints were 2.5 and 7 times greater than the specimens using the commercial angle brackets. A simplified component-based analytical model was also developed to predict the strength of the castellated joints loaded parallel and perpendicular to grain of the CLT outer layers. The simplified model was found to be adequate in estimating strength given the model limitations. Overall, the study showed that these castellated CLT joints can provide one effective connection type with high shear strength and stiffness for CLT structures.